Complications of stapled hemorrhoidectomy - Jain, Pushpendra; Dhakaita, Shyam; Narayan Vishnoi, Shri (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Background: Stapled hemorrhoidectomy (SH), a new approach to the treatment of hemorrhoids, removes a circumferential strip of mucosa about four centimeters above the dentate line. Immediate complications (first week) were: severe pain in all patients, bleeding, thrombosis, urinary retention, anastomotic Dehiscence, fissurePerineal intramural hematoma, and submucosal abscess The most common complication after 1 week was recurrence of hemorrhoids in of patients, severe pain, stenosis, fissure, bleeding, skin tag, thrombosis, papillary hypertrophy, fecal urgency, staples problems, gas flatus and fecal incontinence, intramural abscess, partial dehiscence, mucosal septum, and intussusceptions. The most common complication in the first 25 cases of the surgeon’s experience was the pain. Even though SH and banding are necessary before recommending the procedure. It was a prospective and retrograde study conducted in R.D. Gardi Medical College, Ujjain. Study Duration was from November 2017 to November 2019. All the patients who were post-op (stapled hemorrhoidectomy) case of hemorrhoid disease. The total number of patients operated with stapled hemorrhoidectomy in the 2 years period (2017-2019) was 400.